Creativity-Induced Forms of Non-Verbal Communication in the Process of Vocabulary Internalization in Case of Young Learners - Polok, Krzysztof; Stankiewicz, Olga; Stradiotova, Eva (Papers in Linguistics, 2022)
The study is aimed to answer whether the use of iconic nonverbal gestures positively influences the acquisition of selected vocabulary by young learners. The research entailed 20 young private language school students split into Experimental (G1) group, where students were taught by the use of the gestural method; and Control (G2) group taught the same material using the traditional way of acquiring vocabulary. In both cases, the treatment lasted 4 weeks with two 50 minute-long lessons weekly. To measure the data from the treatment time, the pre-test and the post-test were employed. The t-tests were applied for statistical calculations. The basic measurement instruments, such as mean, mode, median, variance, and standard devotion were analysed. Additionally, the observation sessions were conducted in each group during the third week of the study. The gathered information allowed us to prove the hypothesis that gestures have a positive influence on retention of acquired vocabulary among six-year-old learners.